Counterparties’ Influence on an Enterprise’s Social Capital Formation - Iryna Zhyhlei; Dmytro Zakharov; Ciobanu Ghenadie (Indonesian Journal of Sustainability Accounting and Management, 2020)
The purpose of this study is to determine the influence of counterparties on the formation of an enterprise’s social capital, which is a component of measuring its value. The size of social capital is the result of the synergistic effect of all its components, namely, trust, social networks, and social norms. In this research study, the components of social capital in an enterprise are estimated to be part of the relationship with the stakeholders of the enterprise, including counterparties. Liquidity and financial stability are the criteria for choosing counterparties and for assessing cooperation prospects with them. Additionally, there are rating organizations such as Transparency International Ukraine, whose 2016 results were taken as a basis for the selection of research objects. Organizational transparency and disclosure of data indicate the intention of a company to be open to stakeholders at all levels to increase their confidence. Thus, the level of transparency of activity and the stability of the social network are interdependent. This study examines and analyzes the cooperation of enterprises with other stakeholders to determine its impact on the formation of the social capital of enterprises. The results will provide a basis for the development of a social capital assessment method.